Determinants of fertilizer use in northern Nigeria - Olayide, O.E.; Alene, Arega D.; Ikpi, A. (2009)
Farm-level decision concerning the use of fertilizer is governed by socio-economic and institutional factors, asmuch as by agronomic and ecological concerns. Using data from a sample of 320 farm households in 16 geo-referenced villages, this study assessed the determinants of fertilizer use in northern Nigeria. Results show that the intensity of fertilizer use increases with family labor and physical access to fertilizer, but declines with cultivated land and plot distance from homestead. Consistent with the population-induced innovation hypothesis, the evidence suggests that smallholder farmers use fertilizer more intensively than larger farmers. The study concludes with implications for policy aimed at land use intensification through increased fertilizer use among smallholders.